1984
DOI: 10.1111/j.1600-0528.1984.tb01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status and attitudes to dental care in families participating in a Danish fluoride tablet program

Abstract: The caries experience and dental fluorosis of 84 Danish children, who had used fluoride tablets for 1-4 yr in the period 1976-80, were compared with those of a group matching in sex, age, place of living, and socioeconomic status. The average age of the children at the time of examination was 5.8 yr. A recording of mothers' attitudes to dental care, knowledge about tooth brushing, attitudes to candy, and number of teeth in the maxilla showed no difference between the fluoride tablet group and the non-users' gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In a Copenhagen suburb, an evaluation study has shown that the eect of¯uoride rinsing is poor if a wellestablished dental care system exists and appropriate dental habits are developed in the population [15]. Previous studies [16] have shown that¯uoride tablets and¯uoride chewing gum are seldom indicated in dental health services, the present study con®rms this. Indications for ®ssure sealing have only been described in a few reports [17,18].…”
Section: Discussionsupporting
confidence: 73%
“…In a Copenhagen suburb, an evaluation study has shown that the eect of¯uoride rinsing is poor if a wellestablished dental care system exists and appropriate dental habits are developed in the population [15]. Previous studies [16] have shown that¯uoride tablets and¯uoride chewing gum are seldom indicated in dental health services, the present study con®rms this. Indications for ®ssure sealing have only been described in a few reports [17,18].…”
Section: Discussionsupporting
confidence: 73%
“…Riordan maintains that all these variables can alter the testing results (17). Only a few supplement studies have taken account of factors such as socio-economic status or parent's educational level, but these studies suggest that such variables are more important for caries prevention than the use of supplements (19)(20)(21). According to Spencer "fluoride can prevent caries up to 71%" but just 2% of this reduction is due to the contribution of tablets and the reasons for the low contribution of fluoride supplements were poor efficacy in a time when caries incidence is low, and poor compliance with recommendations to use it (22).…”
Section: Discussionmentioning
confidence: 99%
“…This theory had an interesting later test. A group of 84 children (mean age 5.8 years) who had used supplements for 1 4 years was matched with regard to age, sex, residence, and socioeconomic status with 84 supplement nonusers in a low-fluoride area (136). The mothers' attitudes toward dental care, their knowledge of oral hygene and diet, and their dental status corresponded between the groups.…”
Section: Other Considerationsmentioning
confidence: 99%